The Human Capital Contract: Funding Education through Private Investment in Iceland - Jóel Evert Patreksson Thomas 1993- (2017)
This thesis discusses how the move to knowledge economies has created a need to find alternative ways to fund higher education. With increased pressures on universities to graduate more students, traditional ways of funding education have been shown to be inadequate. Human Capital Contracts are introduced as a viable option, where individual students are granted access to private capital to fund their education. The strength of the human capital contact is that risk is no longer the students alone but shared with investors. The negative aspect of HCCs are seen as legal uncertainty, moral hazard and adverse selection. The thesis concludes with a description of the relevance of HCCs to the Icelandic context. Iceland’s egalitarian and consumer protection oriented social economic and legal environment lend themselves well to the implementation of HCCs as an alternative option for individuals to fund their university education.